Encuentros y desencuentros: Cortázar entre Rimbaud y Mallarmé (El Hilo de la Fabula, 2010)
We propose examining how the notion of (national, idiomatic) dis-identity in an early and enthusiastic essay by Julio Cortázar on Rimbaud and his poetry plays an important role in Cortázar’s poetics of that time and afterwards. Besides, we further propose examining how this same notion, linked to Rimbaud and not to Mallarmé in Cortázar’s essay, becomes instead a central issue in Jacques Rancière’s reading of Mallarmé’s poetics and is nowadays underscored as a fundamental issue in Juan José Saer’s studies of cultural identities in the Rio de la Plata area.